Rationalizing Fabrication and Design Toward Highly Efficient and Stable Blue Light‐Emitting Electrochemical Cells Based on NHC Copper(I) Complexes. (8th March 2018) - Weber, Michael D.; Fresta, Elisa; Elie, Margaux; Miehlich, Matthias E.; Renaud, Jean‐Luc; Meyer, Karsten; Gaillard, Sylvain; Costa, Rubén D.
Abstract: Recently, the use of a new family of electroluminescent copper(I) complexes—i.e., the archetypal [Cu(IPr)(3‐Medpa)][PF6 ] complex; IPr: 1, 3‐bis‐(2, 6‐di‐iso‐propylphenyl)imidazole‐2‐ylidene; 3‐Medpa: 2, 2′‐bis‐(3‐methylpyridyl)amine—has led to blue light‐emitting electrochemical cells (LECs) featuring luminances of 20 cd m −2, stabilities of 4 mJ, and efficiencies of 0.17 cd A −1 . Herein, this study rationalizes how to enhance these figures‐of‐merit optimizing both device fabrication and design. On one hand, a comprehensive spectroscopic and electrochemical study reveals the degradation of this novel emitter in common solvents used for LEC fabrication, as well as the impact on the photoluminescence features of thin‐films. On the other hand, spectro‐electrochemical and electrochemical impedance spectroscopy assays suggest that the device performance is strongly limited by the irreversible formation of oxidized species that mainly act as carrier trappers and luminance quenchers. Based on all of the aforementioned, device optimization was realized using ionic additives and a hole transporter either as a host–guest or as a multilayered architecture approach to decouple hole/electron injection. The latter significantly enhances the LEC performance, reaching luminances of 160 cd m −2, stabilities of 32.7 mJ, and efficiencies of 1.2 cd A −1 . Overall, this work highlights the need of optimizing both device fabrication and design toward highly efficient and stable LECs based on cationic copper(I) complexes. Abstract : New concepts about device fabrication and design toward efficient and stable blue light‐emitting electrochemical cells based on copper(I) complexes are provided. Spectro‐electrochemical and electrochemical impedance spectroscopy assays reveal the degradation mechanism upon device fabrication and the effect of the irreversible formation of oxidized species that act as carrier trappers and luminance quenchers under device operation conditions.